PSII-17 Comparison of corn ethanol co-products from Brazil and USA apparent total tract digestibility of nutrients in pigs - Paula, Vinicius R C (J Anim Sci, 2020)
The objective of this study was to determine the apparent total tract digestibility (ATTD) of DM, GE, EE, NDF, ADF, and CP, the metabolizability of energy, of two high protein (HP) corn distillers dried grain (DDG) and of two corn DDG with solubles (DDGS), from Brazil and USA, and their respective digestible and metabolizable energy content in growing pigs. Fifty crossbred barrows (32.4±6.9kg) were distributed in a randomized block design, with 10 replicates, and received a 96.7 % corn basal diet (BD) or four diets with 40% of each test ingredient: Brazilian HP DDG (BHP); USA HP DDG (UHP); Brazilian DDGS (BDG) and USA DDGS (UDG), substituting for corn. Animals were fed at 2.8 x maintenance (110 kcal of DE per kg of BW0.75) for 7 d adaptation and 4 d of total feces and urine collection. The ATTD of nutrients and energy were calculated by difference and the results were submitted to ANOVA and Tukey’s test (P< 0.05). The BHP and UHP samples contained (as is basis) 92.3 – 89.6% DM, 2.8 – 3.5% ash, 42.9 – 34.9% CP, 10.3 – 7.3% EE, 32.7 – 47.5% NDF, 13.3 – 17.5% ADF, 5.30 – 4.90 Mcal/kg, respectively. The BDG and UDG samples contained (as is basis) 86.1 – 86.1% DM, 4.8 – 4.9% ash, 13.9 – 25.8% CP, 9.0 – 6.4% EE, 40.8 – 40.2% NDF, 13.3 – 14.3% ADF, 4.51 – 4.53 Mcal/kg, respectively. The ATTD of DM and GE and the digestible and metabolizable energy contents of BHP were greater (P< 0.05) than those verified in UHP. The ATTD of DM, GE, NDF, ADF, digestible and metabolizable energy values of BDG were lower (P < 0.05) than those verified in UDG. In conclusion, the BHP presented higher digestible values to almost all parameters evaluated, however, all ingredients presented acceptable digestible contents, indicating they may be used in pigs feeding. [Image: see text]